Rational and Flexible Adaptation of Sentence Production to Ongoing Language Experience - Thothathiri, Malathi (Frontiers in Psychology, 2021)
Whether sentences are formulated primarily using lexically based or non-lexically based information has been much debated. In this perspective article, I review evidence for rational flexibility in the sentence production architecture. Sentences can be constructed via lexically dependent or independent routes depending on the statistical properties of the input and the validity of lexical versus abstract cues for predicting sentence structure. Different neural pathways appear to be recruited for different individuals and verbs with different statistical properties, suggesting that alternative routes are available for producing the same output. Individual differences in cognitive control, or the ability to regulate behavior, may influence the selection of a sentence structure from multiple options. Together, extant evidence indicates that the human brain adapts to ongoing language experience and that the nature of the adjustment depends on the language environment and individual factors.